HIGH-MG LAVAS FROM THE DARIGANGA VOLCANIC FIELD IN THE SOUTHEASTERN MONGOLIA: PETROGENETIC MODEL OF MAGMATISM AT THE ASTHENOSPHERE–LITHOSPHERE BOUNDARY - Irina S. Chuvashova; Sergey V. Rasskazov; Tatiana A. Yasnygina; Ekaterina A. Mikheeva (Геодинамика и тектонофизика, 2015)
It is revealed that high-Mg lavas (MgO=11.0–15.8 wt. %) are spatially controlled by linear zones extending for more than 90 km and demonstrate chemically distinct differences from moderately-Mg compositions (MgO=3.0–11.0 wt. %), which occupy the isometric area of the Dariganga volcanic field. From the major and trace-element data on the rocks in the field under study, we have justified a petrogenetic mode of the uniform one-level mantle magmatism. Our model differs from the contrasting magmatism model of the processes that developed at two levels beneath the Hannuoba volcanic field. Based on tomography images showing the East Mongolian local low-velocity anomaly in the upper mantle, we suggest that magmatism of Type 1 occurred in the mantle sources at the asthenosphere–lithosphere boundary and the underlying asthenosphere as a reflection of a relatively weak mantle flow that may have ascended from a depth of ~250 km. Magmatism of Type 2 occurred in the isolated sources of the sublithospheric mantle and the asthenosphere–lithosphere boundary as an evidence on the initially strong mantle flow that may have ascended from a depth of ~410 km.